オキアミ ルイ ノ グン シュウダン (Swarm) ニ ツイテ - 根本, 敬久; ネモト, タカヒサ; 石丸, 君江; イシマル, キミエ; 白井, 貴子; シライ, タカコ; Nemoto, Takahisa; Ishimaru, Kimie; Shirai, Takako (1981)
P(論文) 海洋のおきあみ類は, 密な群集団を形成する。Euphausia superba, E. pacificaやThysanoessa属の数種が形成する群集団は極海において海の表層にしばしば出現し, 目視により観察される。群集団の種構成は単純で, 南極海域で, 1972/73年度に調査された317の群集団のうちE. superbaとThysanoessa macruraの混合群集団が5例のみ認められ, 他はE. superbaのみからなっていた。Euphausia superbaの円形の群集団の径は平均30m程度であり, 数百m以上に達するものも出現した。おきあみ群集団の生物量は時として30kg/m^3に達することがあるが100g/m^3∿200g/m^3の範囲のものが多い。より小型の個体は単位水量当たりの個体数が増大するが, 単位水量当たりの生物量は大型の個体により形成される群集団の生物量よりも小さい。また, この論文において一般におきあみ群(aggregation)と呼ばれる種々の性状の群に対する英語名に対応する日本語名を提案した。 Euphausiids often form dense swarm in the sea. The surface swarms of Euphausia superba, E. pacifica and some species of Thysanoessa are often observed in the polar waters. The size and density of swarms of euphausiids are various. The average size of round swarms of Euphausia superba in the Antarctic is about 30 metres in diameter sometimes amounting to several hundreds. The species composition of those swarms is simple. It was mostly of Euphausia superba in the research in the 1972/73 season. Five mixed swarms of E. superba and Thysanoessa macrura are observed among 317 swarms studied in the high Antarctic. The biomass of swarm sometimes attains to 30kg/m^3,generally ranging between 100g/m^3 and 200g/m^3. Smaller individuals form heavier dense swarms in individual number, but the biomass per unit volume of sea water is less than the swarm of larger individuals. The relation between the size of zooplankton and micronekton and the density of individual number and biomass of swarms is also discussed. The Japanese common names for the English names of different types of aggregation of euphausiids are proposed to clarify the nature of swarms in the future description and studies. departmental bulletin paper